NEUROPSYCHOLOGIC STATUS OF PATIENTS WITH CERVICAL BACK PAIN - Khodjaeva , Zulfiya Amangeldievna (Educational Research in Universal Sciences, 2023)
Among the adult population, up to 43% have experienced back pain in the past month, up to 65% have experienced back pain in the past year, and approximately 84% have experienced back pain at least once in their lives [2, 10]. Low back pain and neck pain are among the most common causes of disability in the 40-60 age group [6, 11]. Back pain syndromes often develop between the ages of 20 and 50 years, with pain syndromes reaching a maximum between 50 and 64 years of age; between the ages of 20 and 64 years, 24% of men and 32% of women complain of pain in the neck or back [8, 9]. Most interestingly, 12-26% of children and adolescents also complain of neck or back pain [10, 14].